Implementation Of Supply Chain Management And Its Impact On The Efficiency Of Nippo Mechatronics (M) Sdn. Bhd. - Chin, Su Ching (2008)
Supply chain management is an essential concept involving the integration of all the value creating elements in the supply, manufacturing, and distribution processes, from raw materials extraction, through the transformation process, to end user consumption. Therefore, the main purpose of this study is to identify major reason of supply chain management implementation in Nippo Mechatronics (M) Sdn Bhd.